2001
DOI: 10.1078/0944-5013-00091
|View full text |Cite
|
Sign up to set email alerts
|

Studies on composition and stability of a large membered bacterial consortium degrading phenol

Abstract: A ten member microbial consortium (AS) consisting of eight phenol-degrading and two non-phenol-degrading strains of bacteria was developed and maintained in a fed-batch reactor by feeding 500 mg l(-1) phenol for four years at 28 +/- 3 degrees C. The consortium could degrade 99% of 500 mg l(-1) phenol after 24 hours incubation with a biomass increase of 2.6 x 10(7) to 4 x 10(12) CFU ml(-1). Characterization of the members revealed that it consisted of 4 principal genera, Bacillus, Pseudomonas, Rhodococcus, Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…For equivalent initial phenol concentrations, the phenol degradation efficiencies obtained in this work were higher than those reported by Agarry (2008) for the monoculture of indigenous P. aeruginosa and P. fluorescens, respectively. This was in agreement with other workers (Ambujon, 2001;Guieysse et al, 2001;Oboirien et al, 2005;Prpich and Daugulis, 2005) that mixed culture offers an improved performance than mono or pure culture of microorganisms. However, it is in contrast with the observation of Zilli et al (1993).…”
Section: Assessment Of Performancesupporting
confidence: 94%
“…For equivalent initial phenol concentrations, the phenol degradation efficiencies obtained in this work were higher than those reported by Agarry (2008) for the monoculture of indigenous P. aeruginosa and P. fluorescens, respectively. This was in agreement with other workers (Ambujon, 2001;Guieysse et al, 2001;Oboirien et al, 2005;Prpich and Daugulis, 2005) that mixed culture offers an improved performance than mono or pure culture of microorganisms. However, it is in contrast with the observation of Zilli et al (1993).…”
Section: Assessment Of Performancesupporting
confidence: 94%
“…As effective as these TPPBs have been, they do have several limitations, as noted above, which restrict operation to the use of pure strains of organisms. Pure cultures consisting of single strains of microorganisms have shown to be effective in the degradation of phenol (Bandyopadhyay et al 1998;Beshay et al 2002;Hamed et al 2003;Seker et al 1997;Vrionis et al 2002), however, it has also been shown that microbial consortia can offer improved performance (Ambujom 2001;Guieysse et al 2001b). The benefit of using a robust microbial consortium is often due to its capability of degrading a variety of toxic substrates without the accumulation of toxic intermediates (Acuna-Arguelles et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…At present, environmental bioremediation has been used to explore the bacterial consortia role in many different ways. For example, in contaminants such as BTEX (Littlejohns and Daugulis 2008 ), Crude oil (Tang et al 2010 ;RahmanT , P. frederiksbergensis , P. fragi T , P. paucimobilis , P. vesicularis , P. capacia Ambujom 2001 ), Rhodococcus (Ambujom 2001 ), Pedobacter ( P. piscium ), Sphingomonas ( S. paucimobilis Wang et al 2004 ), Stenotrophomonas ( S. rhizophila , S. maltophilia Kim et al 2009 ), Streptomyces (Ambujom 2001 ), and Xanthomonas ( X. maltophilia Wang et al 2004 ), are involved with a high level of effi ciency.…”
Section: Algae-bacteria Interactionsmentioning
confidence: 99%